Enabling places and enabling resources: New directions for harm reduction research and practice - Duff, Cameron (Wiley-Blackwell Publishing Ltd., 2010)
In this digest, Cameron Duff proposes a different way of understanding the risk environment literature as it relates to the implementation of harm reduction. He argues that we need to look beyond the everyday tools of harm reduction like needle and syringe programs and peer education to 'enabling places' and 'enabling resources', areas where public policy makers and social planners can ensure the delivery of more innovative harm reduction policies and programs. Duff urges us to see harm reduction as more than just providing drug users with specific resources to reduce individual drug-related harm. Instead, he argues that we need to make use of the range of material, social and affective resources that are available across the diverse settings in which drug use occurs. © 2010 Australasian Professional Society on Alcohol and other Drugs.